2020
DOI: 10.1007/s11947-020-02461-6
|View full text |Cite
|
Sign up to set email alerts
|

Production, Properties, and Applications of α-Terpineol

Abstract: α-Terpineol (CAS No. 98-55-5) is a tertiary monoterpenoid alcohol widely and commonly used in the flavors and fragrances industry for its sensory properties. It is present in different natural sources, but its production is mostly based on chemical hydration using α-pinene or turpentine. Moreover, many bioprocesses for the microbial production of α-terpineol via biotransformation of monoterpenes (limonene, αand β-pinenes) are also available in the literature. In addition to its traditional use, αterpineol has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(50 citation statements)
references
References 132 publications
3
45
0
2
Order By: Relevance
“…Our analysis with α-TA analytical standard confirmed that such strong antifungal effect of α-TA essential oil could be attributed to the presence of high amount of α-TA and, possibly, the presence of other bioactive chemical compounds such as α-terpineol, geraniol, α-terpinene ( Table 3 ). Antimicrobial activities of α-terpineol and geraniol on different microorganisms were also described in other studies [ 66 , 67 , 68 ]. Interestingly, in our studies, Candida yeasts were generally more resistant to α-TA essential oil α-TA than fungi and dermatophytes.…”
Section: Discussionsupporting
confidence: 53%
“…Our analysis with α-TA analytical standard confirmed that such strong antifungal effect of α-TA essential oil could be attributed to the presence of high amount of α-TA and, possibly, the presence of other bioactive chemical compounds such as α-terpineol, geraniol, α-terpinene ( Table 3 ). Antimicrobial activities of α-terpineol and geraniol on different microorganisms were also described in other studies [ 66 , 67 , 68 ]. Interestingly, in our studies, Candida yeasts were generally more resistant to α-TA essential oil α-TA than fungi and dermatophytes.…”
Section: Discussionsupporting
confidence: 53%
“…Only small amounts of natural terpineol are extracted from essential oils as an isolate. The vast majority is produced from natural pinene by chemical synthesis or biotechnological methods [ 65 ]. Terpineol is widely used in fragrant composition (e.g., lime), household products (e.g., air fresheners, washing powders).…”
Section: The Hidden Ingredients Of Eosmentioning
confidence: 99%
“…Its annual consumption is estimated to be approximately 9.2 tons, which represents an individual intake of 17.2 µg/kg/day in the United States of America (Tai et al 2016;Molina et al 2019c). The traditional commercial uses of α-terpineol include household products, food technology and avor preparations, but the increasing discoveries have been made regarding its bioactivities, such as antioxidant, anticancer, antinociceptive, anticonvulsant and sedative activities (Sousa et al 2020;Sales et al 2020e).…”
Section: Fungal Biotransformation Of Limonene For the Production Of Aroma Compoundsmentioning
confidence: 99%